2011
DOI: 10.1074/jbc.m111.235333
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Region of N-Methyl-d-aspartate Receptor (NMDAR) Subunit Is Required for Receptor Subunit Assembly

Abstract: N-Methyl-D-aspartate receptors (NMDARs), one of three main classes of ionotropic glutamate receptors, play major roles in synaptic plasticity, synaptogenesis, and excitotoxicity. Unlike non-NMDA receptors, NMDARs are thought to comprise obligatory heterotetrameric complexes mainly composed of GluN1 and GluN2 subunits. When expressed alone in heterogenous cells, such as HEK293 cells, most of the NMDAR subunits can neither leave the endoplasmic reticulum (ER) nor be expressed in the cell membrane because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…A recent study showed that the transmembrane regions of the NMDA receptor subunits are necessary for the assembly of NMDA receptors (31). Our electrophysiological data show that the replacements of key amino acid residues within both the NR1 and NR2B M3 domains do not interfere with the formation of the functional NMDA receptors.…”
Section: Discussionmentioning
confidence: 54%
“…A recent study showed that the transmembrane regions of the NMDA receptor subunits are necessary for the assembly of NMDA receptors (31). Our electrophysiological data show that the replacements of key amino acid residues within both the NR1 and NR2B M3 domains do not interfere with the formation of the functional NMDA receptors.…”
Section: Discussionmentioning
confidence: 54%
“…The deletion of the GluN1 M4 segment either blocked (Horak et al, 2008) or permitted (Meddows et al, 2001) surface expression of NMDARs. However, recent experiments have suggested that for NMDAR subunits, the ion channel core (M1–M3) is required for homodimer formation, whereas both the ion channel core and the M4 segment (as well as S2) are necessary for heterotetrameric assembly (Cao et al, 2011). Part of the uncertainty concerning the role of the M4 segment in NMDAR assembly may reflect that it is not required for dimerization but only tetramerization.…”
Section: Discussionmentioning
confidence: 99%
“…Such conformational changes induced by agonist binding to GPCRs have been measured directly using spectroscopic methods, including FRET (14,15). For the NMDAR, a tetrameric receptor composed of two GluN1 and two GluN2 subunits in the hippocampus (7,16), intrareceptor FRET signals from fluorescent molecules connected to the extracellular domain of subunits have been measured and used to monitor the assembly of the receptors (17). However, detection of transmembrane transduction that couples agonist binding to conformational changes at the cytoplasmic domain of the NMDAR has not been attempted.…”
mentioning
confidence: 99%